Local Methotrexate Injection Followed by Dilation and Curettage for Cesarean Scar Pregnancy: A Prospective Non-randomized Study - Tan, Kai-Liang; Chen, Yu-Mei; Zeng, Wei; Meng, Ying; Jiang, Li (Frontiers in Medicine, 2022)
Purpose: To evaluate the clinical effects and outcomes of local intra-gestational sac methotrexate injection followed by dilation and curettage for treatment of cesarean scar pregnancies (CSP). Method: This prospective non-randomized study was conducted on patients diagnosed with CSP between 2018 and 2020 at the Maternal and Child Health Hospital of Guangxi Zhuang Autonomous Region. Patients were categorized into two groups according to the treatments, i.e. local intra-gestational sac methotrexate injection followed by dilation and curettage (group A), and uterine artery embolization in combination with dilation and curettage (group B). The choices of treatment reflect the patients’ decision after they thoroughly understood the benefits and risks of the two therapies. Clinical data were then collected and compared between these two alternatives. Results: Seventy-seven patients with CSP were enrolled in the study. Of this total, 41 versus 36 were respectively categorized into group A and group B. Similar success rates were observed between these two groups (92.7% vs 97.2%; RR=27.362, 95% CI: 0.496-1.51E3, p=0.106). However, the overall occurrence of complications in group A was significant lower when compared with group B (17.1% vs 52.8%; RR=0.236, 95% CI: 0.077-0.728, p=0.012). Lower abdominal pain (unrelated to infection) and intrauterine adhesions were the two primary complications exhibited in group B of the present study, with rates of 38.9% and 22.2% respectively. Conclusions: Local intra-gestational sac methotrexate injection followed by dilation and curettage is an effective and safe treatment for CSP that also drastically reduces the risks of complications. Further multiple center randomized trials with large series are warranted to confirm these findings.